Analisis Semiotika Makna Optimisme pada Lirik Lagu K-Pop NCT Dream “Hello Future” - Farahdila, Zahwa; Utami, Lusia Savitri Setyo (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
Communication is the most important activity for us in life. This is because we as social beings need interaction to convey the contents of our thoughts with others. The process of delivering messages with communication can be done with certain media. One of the media that is often used to convey messages is music. Based on this, a concept called musical communication emerged. Today the world of music is growing all over the world, including K-Pop. One of the music groups currently popular with young Indonesians is NCT Dream. Several NCT Dream songs contain lots of uplifting messages that are channeled to listeners and fans. NCT Dream is a group of singers from South Korea that are currently popular with young people. NCT Dream also delivers encouraging messages through their songs. This study aims to find out the meaning of optimism in the lyrics of the NCT Dream song